An Analysis Of Translation Techniques And Translation Orientations Used ByY The Fifth Semester Students Of Nommensen HKBP UNIVERSITY In Translating Narrative Text From English To Indonesian - Abdi Putra Arianto Simanjuntak; Harpen H.P. Silitonga; Kammer Sipayung (LPPM Universitas HKBP Nommensen, 2026)
This study examines the translation techniques and orientation applied by fifth-semester students of the English Education Study Program at HKBP Nommensen University in translating the narrative text The Legend of Lake Toba from English into Indonesian. Using a descriptive qualitative design supported by quantitative data, the study analyzed 24 students’ translations based on Molina and Albir’s (2002) translation techniques and Nida’s (1964) theory of formal and dynamic equivalence, following Miles and Huberman’s (1994) interactive model.The findings reveal ten translation techniques with 2,016 total occurrences. Literal Translation was dominant (65.63%), followed by Modulation (19.84%) and Amplification (8.09%), while other techniques appeared in minimal percentages. The predominance of Literal Translation indicates a strong source-oriented approach, particularly formal equivalence. Overall, students tend to prioritize structural accuracy over communicative naturalness, suggesting the need to strengthen their understanding of translation orientation and the balanced application of translation techniques in narrative texts.